1986
DOI: 10.1111/j.1574-6968.1986.tb01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Signature fatty acids in the polar lipids of acid-producingThiobacillusspp.: Methoxy, cyclopropyl, alpha-hydroxy-cyclopropyl and branched and normal monoenoic fatty acids

Abstract: The polar lipids of 5 species of Thiobacillus were extracted and purified. An analysis of the fatty acid composition of the polar lipids documented the presence of methoxy, cyclopropyl, monounsaturated and hydroxycyclopropyl fatty acids of sufficiently unusual structure to serve as ‘signatures’ for the presence of these organisms in environmental samples. The structures of the unusual fatty acids of the polar lipids were confirmed by mass spectrometry (MS) after isolation by capillary gas chromatography (GC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nichols et al [14,21] found unusual patterns of unsaturation in the monoenoic PLFA of the methane-oxidizing bacteria and the pathogen Francisella tularensis. With both the acid-forming Thiobacilli [22], and the sulfate-reducing bacteria [23][24][25][26], the monoenic PLFA analysis was very important. These 'signature' patterns were sufficiently unique for detection of these organisms in environmental samples [27,28].…”
Section: Usefulness Of Biomarkers To Define Shifts In Microbial Commumentioning
confidence: 99%
“…Nichols et al [14,21] found unusual patterns of unsaturation in the monoenoic PLFA of the methane-oxidizing bacteria and the pathogen Francisella tularensis. With both the acid-forming Thiobacilli [22], and the sulfate-reducing bacteria [23][24][25][26], the monoenic PLFA analysis was very important. These 'signature' patterns were sufficiently unique for detection of these organisms in environmental samples [27,28].…”
Section: Usefulness Of Biomarkers To Define Shifts In Microbial Commumentioning
confidence: 99%
“…The m/z values in bold correspond to the fragments of the dominant isomers in bacterial phospholipids, whose spectra and fragmentation are presented in Figure 1. Loui and Moore (1979); 4, Kerger et al (1986); 5, Gerwick et al (1987); 6, Orgambide et al (1993); 7, Inamoto et al (1995); 8, Barnathan et al 1998;9, Mesguishe et al 1999;10, Drouin et al 2000. source of essential FAMEs in the microbial loop (Zhukova and Kharlamento 1999).…”
Section: Molecular Patterns Of Flagellate Fatty Acidsmentioning
confidence: 95%
“…True o-methoxy PLFA are known in some bacteria as are PLFA with multiple methyl or polar substituents on the carbon chain [13]. Hydroxy fatty acids with substitution most often at the 2 or 3 position, from the carboxyl, are important biomarkers.…”
Section: Figurementioning
confidence: 99%